Kinerja Pelayanan Angkutan Sungai untuk Penumpang Menggunakan Speedboat dari Buntok ke Kecamatan Janamas Kabupaten Barito Selatan - Florida Astuti Samul; Ina Elvina; Devia Devia (Fakultas Teknik, 2023)
The role of transport is crucial as the population grows. Many river transporters use this river transport route as a round trip access from the city to the district and province. At the beginning of the research, the data collection in this study was by making direct observations (observation) and distributing questionnaires. Then an analysis of the performance evaluation and passenger satisfaction of speedboat transport with the performance formula method and the Importance Performance Analysis (IPA) method with the aim of evaluating service performance and analysing the level of passenger satisfaction with river transport. Based on the results of the evaluation of speedboat river transport performance services for an average load factor of 112.14%, service frequency of 1 vehicle per day, waiting time 30 minutes, travel time 4 hours with a speed of 33.68 km/hour. In the analysis of Importance Performance Analysis on the top priority on the variable availability and appearance of fire extinguishers, availability of buoys, passenger capacity on transport, comfort on the trip, cleanliness in transport, availability of visible departure schedules. Quadrant 1 needs improvement in improving the quality of speedboat transport services.